HUBUNGAN STATUS GIZI DAN ASUPAN MAGNESIUM DENGAN KEJADIAN PREMENSTRUAL SYNDROME (PMS) PADA REMAJA PUTRI[Correlation between Nutritional Status and Magnesium Intake towards Premenstrual Syndrome (PMS) in Female Teenagers] - Kartika Estiani; Triska Susila Nindya (Universitas Airlangga, 2018)
Premenstrual Syndrome (PMS) is a combination of physical, psychological, and emotional disturbance which is related to menstrual cycle that appear 7 to 10 days before menstruation period and disappear when menstruation begins. Nutritional status and magnesium intake can cause premenstrual syndrome. The purpose of this study was to analyze the correlation of seed nutritional status and magnesium intake with premenstrual syndrome. The research used cross sectional study. The sample size was 99 female students in SMAN 4 Surabaya. The data were collected by measuring weight and height to obtain nutritional status variable; 2x24 hours estimated food records to obtain magnesium intake; and questionnaire for premenstrual syndrome case. The data were analyzed using chi-square test. The results of this study showed that there was correlation between nutritional status (p=0,036) and Premenstrual Syndrome (PMS). Besides that, there was also a correlation between magnesium intake (p=0,012) and Premenstrual Syndrome (PMS). Premenstrual Syndrome (PMS) can be caused by overweight and low magnesium intake. It is recommended for female students to prevent overweight status by monitoring their weight every month and increase their intake of high magnesium, food such as apple, spinach, and sweet potato.